OPTIMISASI PENEMPATAN SENSOR AKSELEROMETER DENGAN METODE EFFECTIVE INDEPENDENCE - Ramadhani, Sofyan (Jurnal Jalan Jembatan, 2023)
This research aims to determine the optimal placement of the accelerometer sensor using the Effective Independence (EFI) method. The Balang Island Bridge was used as a study location. In this research, the EFI method is used to optimize the site of the accelerometer sensor by considering various target mode shapes. The EFI method provides alternative optimal sensor placement with the number of sensors corresponding to the number of target mode shapes used in the analysis. However, sensor placement can result in an asymmetrical arrangement, which can result in the inability of sensors on one side of the bridge to detect vibrations from load sources on the other side. In this study, the sensors were placed symmetrically through a mirroring process to overcome this. This research produces five alternative sensor placements that provide flexibility for bridge owners in choosing a configuration that suits the available budget. The results of this research can be a reference for bridge owners to monitor the structural health of bridges accurately with optimal sensor configurations. With this information, bridge owners can make more effective and efficient decisions in implementing the Structural Health Monitoring System, thereby increasing the safety and reliability of the bridge. Key words: accelerometer, optimal sensor placement, effective independence method, mode shapes, structural health monitoring system